Compound Graphemic Units in a Standard Babylonian Cuneiform Writing - Riemschneider, Kaspar K.
ersch. 1977; U8+A = /u’a/,/u’i/, /u’u/; É+UM and É+A = /e’a/, /e’i/, /e’u/; É, É+A, É+UM, É+A+UM = /e’u/.